2014
DOI: 10.1007/s11033-014-3454-5
|View full text |Cite
|
Sign up to set email alerts
|

TNF A −308G>A polymorphism in Moroccan patients with type 2 diabetes mellitus: a case–control study and meta-analysis

Abstract: Type 2 diabetes mellitus (T2DM) is one of causes of mortality and morbidity in Moroccan population. The identification of genes implicated in this disease can help to found a specific treatment and to improve the quality of life for type 2 diabetic patients. In this study we analyze the association between a polymorphism (-308G>A) of TNF A promoter gene and T2DM in Moroccan patients. Five hundred and fifty-one individuals (307 patients with T2DM and 244 controls) were genotyped for this polymorphism by PCR-RFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Finally, five studies reported data that directly relate polymorphism in question with T2DM (Shiau et al [13], Bouhaha et al [15], Guzmán-Flores et al [16], Saxena et al [19], and Sefri et al [20]), one of which also relates it with obese T2DM patients (Bouhaha et al [15]). The general characteristics of the studies included in this review are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, five studies reported data that directly relate polymorphism in question with T2DM (Shiau et al [13], Bouhaha et al [15], Guzmán-Flores et al [16], Saxena et al [19], and Sefri et al [20]), one of which also relates it with obese T2DM patients (Bouhaha et al [15]). The general characteristics of the studies included in this review are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies conducted in Spain, Hungary, and Morocco significant associations between the TNFA -308G/A polymorphism and the risk of T2DM were identified [11, 17, 20]: two of them in patients with other comorbidities such as coronary heart disease [11] and atherosclerosis [17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The -308 G-->A polymorphism of the TNFA promoter gene is involved in the pathophysiology of insulin resistance and GD [ 41 ]. The same polymorphism is a genetic risk factor for the development of type 2 DM [ 42 ]. Individuals who carry the -308A TNFA gene variant have a 23% greater risk of developing obesity compared with controls, and they showed significantly higher systolic arterial blood pressure and plasma insulin levels, supporting the hypothesis that the TNFA gene is involved in the pathogenesis of the metabolic syndrome [ 43 ].…”
Section: Discussionmentioning
confidence: 99%